2017
DOI: 10.1038/nnano.2017.177
|View full text |Cite
|
Sign up to set email alerts
|

Directed emission of CdSe nanoplatelets originating from strongly anisotropic 2D electronic structure

Abstract: Intrinsically directional light emitters are potentially important for applications in photonics including lasing and energy-efficient display technology. Here, we propose a new route to overcome intrinsic efficiency limitations in light-emitting devices by studying a CdSe nanoplatelets monolayer that exhibits strongly anisotropic, directed photoluminescence. Analysis of the two-dimensional k-space distribution reveals the underlying internal transition dipole distribution. The observed directed emission is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
267
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(275 citation statements)
references
References 37 publications
7
267
1
Order By: Relevance
“…Since the first CdSe NPLs were synthesized in 2008 [2], intensive research has revealed several promising properties for optical and electronic applications, including flat surfaces with atomic monolayer control of thickness [2][3][4], fast and narrow fluorescent spectrum [3][4][5][6], large exciton and biexciton binding energies [6,7], high intrinsic absorption [8], large two-photon-absorption cross section [9,10], weak coupling of carriers to acoustic phonons [11], fast and efficient fluorescence resonance energy transfer [12], suppressed multiexciton recombination [13], and highly directional emission [14].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first CdSe NPLs were synthesized in 2008 [2], intensive research has revealed several promising properties for optical and electronic applications, including flat surfaces with atomic monolayer control of thickness [2][3][4], fast and narrow fluorescent spectrum [3][4][5][6], large exciton and biexciton binding energies [6,7], high intrinsic absorption [8], large two-photon-absorption cross section [9,10], weak coupling of carriers to acoustic phonons [11], fast and efficient fluorescence resonance energy transfer [12], suppressed multiexciton recombination [13], and highly directional emission [14].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Their quasi-two-dimensional structure with precise (atomic monolayer) thickness control results in extremely bright and narrow fluorescent emission, which makes them particularly promising for optoelectronic applications. 1,8,[10][11][12][13] On the other hand, the potential of NPLs as building blocks for molecular superstructures with electronic coupling is still unclear. Van der Waals attraction enables the self-assembly of cofacially stacked NPLs, where the inorganic semiconductor alternates with few-nm-thick layers of organic ligands.…”
mentioning
confidence: 99%
“…To reveal the origin of heavy‐ and light‐holes in CdSe NPLs, the band structure in the vicinity of the Γ‐point of the Brillouin zone were simulated with mBJ (modified Beak–Johnson) approximation, which was more accurate than that with GGA+U approximation ( Figure a; Figures S4 and S5 in details in the Supporting Information) . It was found that the simulated band gap was close to the value of the experimental results, and the excitation modes of heavy‐ and light‐holes were clearly observed.…”
mentioning
confidence: 65%